Penerapan Metode Design Thinking Dalam Perancangan UI/UX Aplikasi Manajemen Keuangan - Aditiya, Fajar Rizki; Nuraini, Ririn; Anggun, Anggun; Voutama, Apriade (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The development of digital technology has transformed the way individuals manage their personal finances. Migrant students often face challenges in recording income and expenses, controlling budgets, and maintaining consistent saving habits. This study aims to design a mobile-based financial management application using the Design Thinking approach, which consists of five main stages: empathize, define, ideate, prototype, and testing. Observations and interviews were conducted with four migrant students to understand their financial management habits and challenges. The results of the user needs analysis were translated into an intuitive UI/UX design with key features such as transaction recording, budget reminders, and financial reports. Usability testing using the System Usability Scale (SUS) indicated that the application has a high level of ease of use and can enhance individual financial management effectiveness. Thus, this study is expected to contribute to the development of digital solutions that assist individuals in achieving financial stability